Iberoromania : Revista dedicada a las lenguas, literaturas y culturas de la Península Ibérica y de América Latina (De Gruyter, 1969)
Iberoromania is the oldest journal in the German-speaking world dealing specifically with the Ibero-Romance languages and literatures of Europe and America. In addition, the journal has become increasingly open to Ibero-Romance languages and literatures outside of Europe and America, above all in African countries.